IMPLEMENTATION OF THE MEDIATION PROCEDURE IN RESOLVING CONFLICT SITUATIONS IN OCCUPATIONAL PATHOLOGY IN ORDER TO INCREASE THE EFFICIENCY OF DISPUTE RESOLUTION - Гаврылышена, Ксения Валерьевна; Семенихин, Виктор Андреевич; Филимонов, Сергей Николаевич; Часовских, Елена Владимировна (Medicine in Kuzbass, 2022)
The high prevalence of occupational diseases among workers employed in the coal mining industry causes the problem of renting employees to establish an occupational disease, and in case of refusal due to the disease with the profession, the number of applications to the judiciary increases.Often, due to low awareness of the possibility of out-of-court settlement of disputes with Occupational Pathology Centers, patients immediately file a lawsuit in court, which can put a significant emotional and economic burden on them.The aim of the research – consider the use of the mediation procedure to resolve contentious issues at the pre-trial level in the field of occupational pathology.Research methods. Dialectical method of cognition, general scientific, methods of comparison, analysis and synthesis.Conclusion. The help of an experienced professional mediator with a legal education during the mediation procedure will allow you to resolve such disputes in the field of occupational pathology at the pre-trial level, which will positively affect not only the economic and emotional side, but also the legal sphere, since the resolution of disputes at the pre-trial level will help reduce the burden on courts.
Keywords: occupational pathology; dispute resolution; mediation; examination of the connection of the disease with the profession